Cover Image. Issue 1 (15th December 2017) - Garseth, Å H; Gjessing, M C; Moldal, T; Gjevre, A G
Abstract : The cover image, by Å H Garseth et al ., is based on the Original Article A survey of salmon gill poxvirus (SGPV) in wild salmonids in Norway, DOI:10.1111/jfd.12688 . Image Credit: Norwegian Veterinary Institute.